Ethnomathematics: Integration of Mathematical Concepts in The Preparation of Cireng Isi, a Traditional West Javanese Food - Harry Dwi Putra; Sendi Ramdhani (Yayasan Keluarga Guru Mandiri, 2025)
Mathematics is closely related to human activities and can be found in everyday life, including traditional food production. Mathematics learning becomes more meaningful when linked to contextual objects familiar to students, such as regional specialty foods. This study aims to identify and analyze mathematical concepts in making cireng isi, a traditional West Javanese food, to integrate them into mathematics learning. This research employs a qualitative descriptive method with an ethnographic approach. Data were collected through observations at the production site, interviews with cireng isi makers, and documentation of the production process. The findings indicate that the making of cireng isi involves the application of social arithmetic concepts in pricing and plane geometry concepts in its physical shapes, including circles, semicircles, trapezoids, rectangles, triangles, and kites. The study concludes that traditional food can serve as an effective learning medium for understanding mathematical concepts contextually. This study contributes to education by providing an alternative ethnomathematical-based approach that enhances student engagement and strengthens their comprehension of mathematical concepts through local culture.